Environmental screening of water associated with shale gas extraction by fluorescence excitation emission matrix. Issue 10 (13th July 2022) - Peers de Nieuwburgh, Camille; Watson, Jonathan S.; Weiss, Dominik J.; Sephton, Mark A.
Abstract : We present a simple method for the screening of recovered water from shale gas extraction that can be used to avoid contamination incidents. Abstract : The shale revolution has involved the production of oil and gas from shale reservoirs enabled by modern techniques such as horizontal drilling and hydraulic fracturing. Large volumes of water-based fluids are required for hydraulic fracturing, some of which return to the surface as produced water. The recycling and effective disposal of produced water reduces water demand and avoids environmental impacts, respectively. Yet risks of water quality degradation surrounding shale oil and gas extraction operations remain highest during produced water treatment and disposal. Risk assessments related to produced water use are difficult to generate due to a lack of standard monitoring methods to characterise produced water and a lack of baseline monitoring data of surrounding water resources. We have performed a study on laboratory shale leachates using fluorescence excitation emission matrix (EEM) spectra and have demonstrated the utility of this spectroscopic technique as a standard method for environmental screening in which the chemical constitution of produced water is monitored. EEM spectra recorded in this work show that dissolved organic matter (DOM) in laboratory shale leachates contains chromophores such as humic acid-like and soluble microbial-like material. Short emission wavelengths (<380 nm) EEM spectra may indicate anthropogenic contamination incidents in future operations, especially as they correspond to fluorescence signatures of some injection fluid additives. Our simple fluorescence method requires little sample preparation and could be coupled with remote sensors for real time, in situ monitoring of contamination incidents.